1966
DOI: 10.1016/0029-5582(66)90435-4
|View full text |Cite
|
Sign up to set email alerts
|

Shell-model calculations on odd-parity levels of nuclei in the range 33S−41Ca

Abstract: The shell model is used to investigate quantltahvely some odd-parity levels of nuclei m the range z~S-41Ca An inert z°-S core Is assumed w~th a residual two-particle interaction of the outer nucleons. Only one nucleon ~s considered to be in the lfff shell, while the others are m "the ld k shell. The interaction matrix elements are reduced to hnear expressions m 14 parameters (i e 12 two-particle interactions and two binding energies to the core)The numerical results are presented as they are obtained from fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Furthermore a state at 3 516 keV, which we do not observe is known to have JS=3/2-. A shell model calculation on the odd parity levels in 37Ar has been made by Erne [18], who assumed an inert 32S core. The outer nucleons were considered to be in the 1d3#% and lf,,* shells, with the restriction that only one nucleon was allowed to be in the lf,/2 orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore a state at 3 516 keV, which we do not observe is known to have JS=3/2-. A shell model calculation on the odd parity levels in 37Ar has been made by Erne [18], who assumed an inert 32S core. The outer nucleons were considered to be in the 1d3#% and lf,,* shells, with the restriction that only one nucleon was allowed to be in the lf,/2 orbit.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of these with matrix elements determined from experiment by Erne (1966) was even more impressive. The comparison of these with matrix elements determined from experiment by Erne (1966) was even more impressive.…”
Section: Fifty Years Of the Shell Model 193mentioning
confidence: 87%
“…Recent measurements in the upper region of the s -d shell have shown that the high-spin negative-parity states in "Si can be well represented by the simple rotational model (Viggars et a1 1973), while in 37Ar they can be explained by the core-excitation model (Gadeken et a1 1974). The high-spin negativeparity states in 37Cl cannot however be explained by either of these models or the simple shell-model calculations available at present (eg Erne 1966).…”
Section: Introductionmentioning
confidence: 91%
“…The E3 strength of the ground-state transition is 13 & 1 Wu which is in good agreement with the 38Ar (3-+ 0') E3 transition strength of 16&6 Wu. Shell-model calculations using an inert ',S core have been performed by Erne (1966) and Maripuu and Hokken (1970). Ern6 allowed one particle to be excited into the If,,, orbital while the other calculation allowed one particle to be excited into either the If,,, or the 2p3/, orbital.…”
Section: --mentioning
confidence: 99%